Creativity in Australian health and physical education curriculum and pedagogy. Issue 5 (13th June 2021) - Welch, Rosie; Alfrey, Laura; Harris, Anne
ABSTRACT: Notions of creativity are increasingly central to educational scholarship and policies, but few studies attend to the intersection between Health and Physical Education (H/PE) and creativity . In this paper we explore the literature on creativity in education and identify how creativity is represented across a broad spectrum of enquiry yet limited in relation to specifically H/PE. Writing from an Australian context, we examine how the key ideas and propositions from the Australian Curriculum for Health and Physical Education and the Critical and Creative Thinking capability raise important questions regarding the social emergence of educative creative purpose and potential in H/PE. We outline the utility of a 'creative ecologies' conceptual framework to consider contemporary practices in H/PE, and apply this to two purposively selected resources; to showcase their contextual eminence for creative learning in H/PE pedagogy and practice. The first resource, Phenomenom!, was funded by Horticultural Innovation Australia to develop food literacy and is linked to cross-curriculum learning outcomes. The second resource, Fitter. Faster. Better, is a St Martin's Youth drama-arts performance where students were prompted to design and perform a fitness programme for adults. Utilising the creative ecologies framework we illustrate the complexity of interconnected creative processes in H/PE as a series of networked elements and cultural flows (policies, practices, products, process, material environments, and partnerships). This framework is then used to identify how the two educational resources exemplify and open up a socially creative practice in both H/PE and everyday life. Our theoretical developments offer new ways to identify, design and enact quality creative and contemporary socio-cultural H/PE curriculum within a broader creative ecology.